1985
DOI: 10.1161/01.res.56.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Fate of intercellular junctions in isolated adult rat cardiac cells.

Abstract: SUMMARY. Freeze fracture and thin section techniques have revealed morphological changes in gap junctions and intercalated discs of adult rat myocytes following enzymatic dissociation. Cell separation leaves behind small vesicular remnants of formerly adjacent cells connected to the intact cell by gap junctions; in contrast, desmosomes cleave at the region of intercellular contact. Apparently, the next step in gap junction breakdown is intemalization of the remnants. In thin section, lanthanum penetration reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 32 publications
8
48
1
Order By: Relevance
“…Early ultrastructural analyses revealed large vesicular double-membrane GJ structures, AGJs, in the cytoplasm of cells derived from many different tissues (Ginzberg and Gilula, 1979;Larsen et al, 1979;Pfeifer, 1980;Leach and Oliphant, 1984;Mazet et al, 1985;Severs et al, 1989). Here, we demonstrate by expressing Cx43-GFP (a major GJ subunit protein) in HeLa cells, that entire GJ plaques can be internalized into one of the coupled cells to form these cytoplasmic, double-membrane GJ vesicles (Figure 1).…”
Section: Formation Of Double-membrane Gj Vesiclesmentioning
confidence: 59%
See 1 more Smart Citation
“…Early ultrastructural analyses revealed large vesicular double-membrane GJ structures, AGJs, in the cytoplasm of cells derived from many different tissues (Ginzberg and Gilula, 1979;Larsen et al, 1979;Pfeifer, 1980;Leach and Oliphant, 1984;Mazet et al, 1985;Severs et al, 1989). Here, we demonstrate by expressing Cx43-GFP (a major GJ subunit protein) in HeLa cells, that entire GJ plaques can be internalized into one of the coupled cells to form these cytoplasmic, double-membrane GJ vesicles (Figure 1).…”
Section: Formation Of Double-membrane Gj Vesiclesmentioning
confidence: 59%
“…Additional studies have shown that docked connexons cannot be separated under physiological conditions (Goodenough and Gilula, 1974;Ghoshroy et al, 1995), suggesting that GJ degradation could occur via the internalization of complete double-membrane spanning GJ plaques. Structural and ultrastructural analyses of differentiating tissues and cells in culture have shown cytoplasmically located, double-membrane GJ vesicles that were termed annular gap junctions (AGJs; Ginzberg and Gilula, 1979;Larsen et al, 1979;Leach and Oliphant, 1984;Mazet et al, 1985;Jordan et al, 2001), leading to the hypothesis that AGJ vesicles represent internalized GJs.To test this hypothesis, we investigated the spatiotemporal process of GJ degradation in living and fixed HeLa cells that transiently or stably expressed fluorescent proteintagged Cx43 (Cx43-green fluorescent protein [GFP], -cyan fluorescent protein [CFP], and -yellow fluorescent protein [YFP]). We then examined these cells by time-lapse fluorescence microscopy combined with ultrastructural analyses.…”
mentioning
confidence: 99%
“…Recently, Fujimoto et al (13) suggested that the alteration of charge on the gap junction membrane may cause the breakdown of gap junctions. Furthermore, based on the report by Mazet et al (22) that the final stage in the breakdown of gap junctions may be evoked by the hypertonicity in enclosed junctional vesicles or the low level of Ca++, Fujimoto et al (13) hypothesize that the alteration of charge on the annular gap junction, which influences the permeability of ions through a channel, may cause the hypertonicity in annular gap junctions or the low level of Ca++.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations suggest that an alteration in the charge on the internalized gap junction, which influences the permeability of ions through a channel, may occur prior to morphological changes, and is assumed to be one reason to hypothesize large osmotic differences across the gap junctional vesicles. Thus the intravesicular condition speculated by Mazet et al (36) would result from the alteration of the charge. Furthermore, we have recently observed the disappearance of cyclase activity on the inside and/or both side membranes of the internalized gap junctions in rabbit ovarian granulosa cells (38).…”
Section: High Density Distribution Of Anionic Sitesmentioning
confidence: 90%
“…Our findings suggest that the electrostatic condition of the gap junction changes during the process. Mazet et al (36) suggest that the final stage in the breakdown of the gap junction may be caused either by the hypertonicity in enclosed junctional vesicles or the low level of Cat+. Our observations suggest that an alteration in the charge on the internalized gap junction, which influences the permeability of ions through a channel, may occur prior to morphological changes, and is assumed to be one reason to hypothesize large osmotic differences across the gap junctional vesicles.…”
Section: High Density Distribution Of Anionic Sitesmentioning
confidence: 99%